Passive impact/vibration control and isolation performance optimization for space noncooperative target capture. (7th January 2020) - Sun, Chong; Hou, Xiaolei
On-orbit capture is an important technique for the space debris removal, refueling, or malfunction satellite repairing. While due to the uncertainty of the motion parameters of the space noncooperative target, the impact between the capture device and the noncooperative target during the capturing process is inevitable, which may bring strong vibration perturbation to the base satellite, and potentially alter the position and the attitude of the servicing spacecraft, or even cause failure of on-orbit tasks. This article presents a new and alternative method for passive suppression of spacecraft impact and perturbation during noncooperative spacecraft capture. The passive device based on bioinspired X-shape is installed between the satellite and the capture device. In the capture process, nonlinear damping of the passive isolation structure can significantly reduce impact/vibration perturbation. For performance analysis, dynamic equations of the isolation system are established. Based on which, the relationship between structure parameters and isolation performance is systematically analyzed. Experiments are conducted for verification of the effectiveness of the proposed method. Moreover, an optimal process using the non-dominated sorting genetic algorithm II optimization method is developed to minimize impact/vibration perturbation effect, and optimal solutions can provide useful reference for the passive isolation system design.